Considerations concerning targetry for radioisotope production at the NAC and the production of gallium-67, indium-111 and cadmium-109 - Nortier, F. M.(Francois Meiring) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1990.